Association of Competence, Motivation and Nurse Workload with Nurse Performance at Mental Hospital in Bali Province - I Nengah Budiawan; Ketut Suarjana; I Putu Ganda Wijaya (Public Health and Preventive Medicine Archive, 2015)
Background and purpose: Average Bed Occupation Rate (BOR) of Mental Hospital in Bali Province in 2014 amounted to 85.3% with an average length of stay about 50 days. Preliminary study indicated inadequate performance of nurses at Mental Hospital in Bali. The purpose of this study was to determine the association of competence, motivation and nurses workload with the performance of nurses in wards of Mental Hospital in Bali Province. Methods: This research was a cross sectional survey. The subjects of the study consisted of all nurses in the inpatient unit, amounting to 111 people. Data were collected using self-administered questionnaires and observation sheet filled out by the head of the room. Data were analyzed using bivariate with chi-square test, and multivariate with logistic regression method. Results: Bivariate analysis showed significant association between the performance of nurses with competence and motivation (p<0.001), however no association with workload (p=0.94). Multivariate analysis showed that the performance of nurses was associated with competence with AOR=65.38 (95%CI: 6.88-621.52) and with motivation (AOR=61.71; 95%CI: 7.15-532.59), however was not significantly associated with workload (AOR=1.012; 95%CI: 0.32-3.17). Conclusion: The performance of nurses was significantly associated with competence and motivation, however not associated with workload.